Decolonizing Western Christianity for a Genuine Catholicity of Culture. Issue 1 (5th April 2019) - Abraham, Susan
Abstract : Does Robert Schreiter's proposal for a new catholicity secure a decolonized theology of culture? This essay discusses salient elements of Schreiter's theological proposals and suggests that postcolonial theologies of culture avoid the twin pitfalls of identity politics and erasure in the Western academic study of theology by employing the methods of deconstruction. Identity claims, knowledge claims, and theological claims are to be persistently critiqued for their tendency towards totalization. Only such a practice of deconstruction aiding an active spirituality can secure a decolonized theology of culture.